Colocalization properties of elementary Ca2+ release signals with structures specific to the contractile filaments and the tubular system of intact mouse skeletal muscle fibers - Georgiev, Tihomir; Förderer, Moritz; Fink, Rainer; Vogel, Martin (Journal of structural biology, 2015)
Ca2+ regulates several important intracellular processes. We combined second harmonic generation (SHG) and two photon excited fluorescence microscopy (2PFM) to simultaneously record the SHG signal of the myosin filaments and localized elementary Ca2+ release signals (LCSs). We found LCSs associated with Y-shaped structures of the myosin filament pattern (YMs), so called verniers, in intact mouse skeletal muscle fibers under hypertonic treatment. Ion channels crucial for the Ca2+ regulation are located in the tubular system, a system that is important for Ca2+ regulation and excitation-contraction coupling. We investigated the tubular system of intact, living mouse skeletal muscle fibers using 2PFM and the fluorescent Ca2+ indicator Fluo-4 dissolved in the external solution or the membrane dye di-8-ANEPPS. We simultaneously measured the SHG signal from the myosin filaments of the skeletal muscle fibers. We found that at least a subset of the YMs observed in SHG images are closely juxtaposed with Y-shaped structures of the transverse tubules (YTs). The distances of corresponding YMs and YTs yield values between 1.3μm and 4.1μm including pixel uncertainty with a mean distance of 2.52±0.10μm (S.E.M., n=41). Additionally, we observed that some of the linear-shaped areas in the tubular system are colocalized with linear-shaped areas in the SHG images.
Im Titel ist die Zahl 2 und das Zeichen + hochgestellt
Gesehen am 10.08.2021